Animals/Artists: Review of Steve Baker, Artist | Animal - Gigliotti, Carol (Humanimalia, 2014)
Steve Baker, Artist | Animal (Posthumanities 23). Minneapolis & London: University of Minnesota Press, 2013. 320 pp. 29.95pb.